Education for health in early adolescence to face the changes physical and emotional - Fernández Arias, María José (2018)
The stage of adolescence is known to involve a lot of changes; these are concentrated in different areas from physical to psychological and emotional according to the sub-steps that they face. Health education for adolescents is a problem for public attention and a challenge for the performance of nursing, mainly due to the fact that adolescence is a stage of life marked by intense physical, emotional and great sociocultural transformations that They last from puberty to adult life. Age-appropriate accompaniment by trained professionals is the key to reducing risk factors for the stage and for children to feel confident about themselves and the way they are going to face them. The objective of this brief review is to analyze the best available scientific evidence in relation to health education regarding changes in early adolescence, taught by nursing to improve the adolescent's coping with these changes. The methodology recommended for Clinical Practice based on evidence was used as a methodology, initially a prognostic type clinical question was posed and the objectives according to this were raised, based on which a set of descriptors was identified from the that the search for scientific evidence was made in different scientific databases.iptors was identified from which it was made the search for scientific evidence in different scientific databases.